2006
DOI: 10.1055/s-2006-944831
|View full text |Cite
|
Sign up to set email alerts
|

An increase in the serum amylase level in patients after peroral double-balloon enteroscopy: an association with the development of pancreatitis

Abstract: Hyperamylasemia after peroral DBE occurs frequently and may be associated with development of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
3
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 7 publications
4
52
3
1
Order By: Relevance
“…Honda et al found asymptomatic hyperamylasemia in 5 of 13 patients after antegrade DBE. One of 13 patients developed pancreatitis [25] . Several mechanisms c o u l d b e r e s p o n s i b l e f o r t h e d e v e l o p m e n t o f hyperamylasemia or pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Honda et al found asymptomatic hyperamylasemia in 5 of 13 patients after antegrade DBE. One of 13 patients developed pancreatitis [25] . Several mechanisms c o u l d b e r e s p o n s i b l e f o r t h e d e v e l o p m e n t o f hyperamylasemia or pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic DBE is accompanied by complications in < 1 % of cases. Hyperamylasaemia has been documented in up to 50 % of patients [157], but clinically significant pancreatitis occurs in only 1 %, almost exclusively after use of the oral insertion route [158,159]. Therapeutic balloon enteroscopy with balloon dilation of strictures has a reported perforation risk of 0 % -3 %, which is comparable to dilation of colonic Crohnʼs strictures [160,161].…”
Section: Balloon-assisted Enteroscopy (Bae)mentioning
confidence: 99%
“…None of the eight patients undergoing retrograde DBE showed elevations of pancreatic enzymes, whereas enzyme elevations were observed in 12 of the 48 patients (25%), six of them being hospitalized due to frank pancreatitis after antegrade DBEs. Honda et al (25), who reported their experience with 13 patients, found that six of them (46%) developed pancreatic enzyme elevations and one developed acute pancreatitis, but this finding and its implications are addressed in a separate study.…”
Section: Discussionmentioning
confidence: 98%